Investigation of the Porosity of Poly(sodium methacrylate) Hydrogels by 1H‐NMR T2‐Relaxation and Inverse Size‐Exclusion Chromatography. Issue 1 (9th December 2020) - Pfeifer, Christoph; Cavalli, Federica; Huber, Birgit; Theato, Patrick; Barner, Leonie; Wilhelm, Manfred
Abstract: A series of poly(sodium methacrylate) hydrogels, also called superabsorbents, having a theoretical degree of neutralization of 100 mol%, and degree of crosslinking varying from 0.6 to 20 mol%, are synthesized via conventional free radical polymerization. The networks are characterized in detail by inverse size‐exclusion chromatography and 1 H‐NMR relaxometry in order to place particular emphasis on the investigation of the pore size distribution (PSD) and the chain mobility, respectively. The two previously mentioned parameters are compared to understand the correlation between the elastic chain mobilities and the average pore size of the hydrogel. From the resulting data, a new empirical equation is proposed, which is valid under the given experimental conditions and permits a rough estimation of the average PSD from the relaxation data. Thus, the equation permits to reduce the number of analytical techniques needed for the characterization of complex systems such as polymer networks. Abstract : Poly(sodium methacrylate) hydrogels, having a degree of crosslinking varying from 0.6 to 20 mol%, are synthesized via conventional free radical polymerization. The network structure is characterized by inverse size‐exclusion chromatography and 1 H‐NMR relaxometry to understand the correlation between the elastic chain mobilities and the average pore size of the hydrogel.